Bahasa Inggris - Nakita Chairunnisa; Wira Dharma; Alia Rizki (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates greenhouse gas (GHG) emissions, with a focus on carbon monoxide (CO), in Banda Aceh City to identify their sources and spatial distribution. Google Earth Engine (GEE) was utilized to process and analyze Sentinel-5P satellite data from November 2023 to November 2024. The results indicate that CO emissions are mainly generated by transportation, industrial activities, and forest fires, reflecting the significant influence of human activities on air quality. Spatial analysis reveals that northern coastal sub-districts, including Kutaraja, Kuta Alam, and Syiah Kuala, experience the highest CO concentrations, while Meuraxa and Jaya Baru show moderate levels, and southern and inland sub-districts such as Banda Raya, Ulee Kareng, and Lueng Bata exhibit low concentrations. The distribution pattern highlights the role of population density, economic activity, and land cover in shaping emission intensity. By leveraging near real-time satellite monitoring, this study provides detailed emission mapping that can guide urban air quality management and climate mitigation strategies. These findings serve as a valuable reference for policymakers and researchers in formulating emission reduction measures and enhancing climate resilience in urban environments.